2016
DOI: 10.1038/srep30698
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Isoform of Human Lynx1 (SLURP-2): Spatial Structure and Pharmacology of Interactions with Different Types of Acetylcholine Receptors

Abstract: Human-secreted Ly-6/uPAR-related protein-2 (SLURP-2) regulates the growth and differentiation of epithelial cells. Previously, the auto/paracrine activity of SLURP-2 was considered to be mediated via its interaction with the α3β2 subtype of the nicotinic acetylcholine receptors (nAChRs). Here, we describe the structure and pharmacology of a recombinant analogue of SLURP-2. Nuclear magnetic resonance spectroscopy revealed a ‘three-finger’ fold of SLURP-2 with a conserved β-structural core and three protruding l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…Cell growth was assayed using the WST‐1 colorimetric test as described elsewhere (Lyukmanova et al ., ,b). WST‐1 (water soluble tetrazolium salt 1; Santa Cruz, Dallas, USA) and 1‐m‐PMS (1‐methoxy‐5‐methylphenazinium methyl sulfate, Santa Cruz) were added to cell in concentrations of 0.25 mM and 5 μM, respectively, for 1 h, and formation of coloured product was measured in the 440–460 nm spectral range using microplate reader (Uniplan, ZAO Pikon, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell growth was assayed using the WST‐1 colorimetric test as described elsewhere (Lyukmanova et al ., ,b). WST‐1 (water soluble tetrazolium salt 1; Santa Cruz, Dallas, USA) and 1‐m‐PMS (1‐methoxy‐5‐methylphenazinium methyl sulfate, Santa Cruz) were added to cell in concentrations of 0.25 mM and 5 μM, respectively, for 1 h, and formation of coloured product was measured in the 440–460 nm spectral range using microplate reader (Uniplan, ZAO Pikon, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…Some of these proteins, such as Lynx1 and Lypd6 in the brain, are membrane‐tethered, whereas others such as the secreted Ly6/uPAR proteins SLURP‐1 and SLURP‐2, are secreted by epithelial tissues and probably involved in the development of a number of skin diseases including Mal de Meleda (Allan et al ., ; Perez and Khachemoune, ) and psoriasis (Tsuji et al ., ). For example, SLURP‐1 inhibits proliferation of human oral keratinocytes (Het‐1A cells) via selective interactions with non‐neuronal α7 type nAChRs (α7‐nAChRs) (Arredondo et al ., ; Lyukmanova et al ., ), while SLURP‐2 could either inhibit or promote cell growth via signalling through different subtypes of nAChRs and muscarinic acetylcholine receptors (M receptors) (Lyukmanova et al ., ). Using electrophysiological recordings in Xenopus laevis oocytes, we showed that SLURP‐1 is an antagonist of α7‐nAChRs, while SLURP‐2 inhibits α3β2 and α4β2 nAChRs but, at concentrations below 100 nM, can activate α7‐nAChRs in presence of ACh (Lyukmanova et al ., ,b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The LY6 prototoxin family consists of small modulatory proteins that can interact with, numerous targets, including nAChRs and muscarinic ACh receptors (see Tsetlin, ; Lyukmanova et al, ). We here only report the effect of these proteins on the modulation of nAChR signalling.…”
Section: Chaperone Proteinsmentioning
confidence: 99%
“…Affinity purification of cortical extracts has revealed that SLURP‐2 can interact with α3, 4, α5, α7, β2, and β4 nAChR subunits and has a broad pharmacological profile. In particular, it inhibits ACh ‐evoked currents of α4β2 and α3β2 ‐nAChRs in oocytes and can enhance or inhibit (at higher concentrations) ACh‐evoked currents of the α7 subtype (Lyukmanova et al, ).…”
Section: Chaperone Proteinsmentioning
confidence: 99%